Frontiers in Statistical Quality Control 9 - Lenz, Hans-Joachim; Wilrich, Peter-Theodor; Schmid, Wolfgang (Frontiers in Statistical Quality Control,, 2010)
The twenty-three papers in this volume are carefully selected, reviewed and revised for this volume, and are divided into two parts: Part 1: "On-line Control" with subchapters 1.1 "Control Charts" and 1.2 "Surveillance Sampling and Sampling Plans" and Part 2:"Off-line Control".